Typical employment subject to mandatory social security contributions remains the norm - Michael Arnold; Anselm Mattes; Gert G. Wagner (DIW Economic Bulletin, 2016)
Since the 1980s, in West Germany has been a substantial decline in the number of people of working age who are not in paid employment. Accordingly, the share of 18- to 67-year-olds without a job has also fallen. This increase in employment figures primarily benefited those in marginal employment or solo entrepreneurs and had less of an impact on those in typical employment. In fact, the present analysis based on data from the German Socio-Economic Panel Study (SOEP), shows that there has been no decline in the share of those of working age who are in typical employment. However, individuals in atypical employment are exposed to some very specific risks. There are various possible measures that may help counteract this type of employment, including abolishing the special legislation on "mini-jobs" (salary of up to 450 euros per month), expanding childcare options, and introducing mandatory retirement and accident insurance for the uninsured self-employed.
Keywords: E24; J21; Z13; 330; labor force participation; middle class; atypical employment; SOEP